Illusive 2 : contemporary illustration and its context. - Klanten, Robert, 1964-; Hellige, Hendrik, ....- (Berlin : Gestalten, 2007)
Since we published Illusive, our first collection of contemporary illustration from around the world, the demand for work in this medium has continued to grow - and with it its range of application and forms of expression. This positive development is confirmed by the exciting work of international illustrators that we have seen since its publication, and it was thus a logical step to present the best of these new works in Illusive 2. The book features an impressive variety of illustration styles and new design approaches that have become more differentiated and complex in comparison to the spontaneous-looking scribbles of years past.
Keywords: Illustraties